The development and validation of a character education model through traditional games based on the Socratic method in an elementary school - Anne Hafina; Lutfi Nur; Arief Abdul Malik (LPMPP Universitas Negeri Yogyakarta, 2022)
This study intended to build a character education model in an elementary school using traditional games based on the Socratic Method. This study used design-based research (DBR), with five experts helping to validate the character education model using a model evaluation instrument and 26 students participating in the model trial. As a result, the developed model comprises six elements: focus, syntax, reaction principles, social system, support system, and application. Meanwhile, the syntax, which consists of four steps: the initial stage, the transition stage, the working stage, and the termination stage, is the core of this model. Experts strongly agree that the model is in the